Pengaruh Karakteristik Pekerjaan, Fasilitas Kerja Terhadap Kinerja Karyawan Pt. Bank Tabungan Negara Cabang Medan Helvetia Medan - Daniel Napitupulu (Jurnal Manajemen Dan Akuntansi Medan, 2019)
Along with the changes so quickly in aspects of their life, then every company should be able to respond rapidly and the demands was that the more complex the employee desires. State Savings Bank or BTN is Indonesian State-Owned Enterprises in the form of a limited liability company and is engaged in the banking and financial services. Employee performance is a determinant of progress or decline of a company. Performance of employees in the company in karekateristik seen through the work given to employees and the company is also working facilities provided by the company. Hypothesis Test Results karekateristik variable work on employee performance characteristics of jobs obtained results (X1) partially have significant influence on employee performance (Y) PT. Savings Bank Negara (Persero) Tbk Branch Cabang Medan Helvetia Medan. t value obtained for 7949 with a probability value t (Sig) is 0.000 (Sig. <?0, 05). Test results hypothesis variable working facilities to employees performance results obtained working facilities (X2) partially have significant influence on employee performance (Y) PT. Savings Bank Negara (Persero) Tbk Branch Cabang Medan Helvetia Medan. t value obtained was 5,077 with a probability value t (Sig) is 0.000 (Sig. <?0, 05). Calculated F value = 208.648 with a probability value of F (sig) is equal to 0.000 (sig.0, 000 ? ?0, 05). Thus Ho is rejected and Ha accepted. It can be concluded that the characteristics of the job (X1) and working facilities (X2) simultaneously have a significant influence on employee performance (Y) BTN (Persero) Tbk, Cabang Medan Helvetia Medan Branch.